Digitalization of Women's Fiqh Da'wah via Instagram Account @dailyhaid - Aizzatul Inayah; Retpitasari, Ellyda; Moh Shofiyul Huda MF; Lukman Hakim; Baudica Setia Noveluis (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2024)
The social media content presented to the public is increasingly varied, including the content of the celebrity, one of which relates to female fiction. The purpose of this research is to describe how @dailyhaid accounts deliver the message about women's fiqh and to analyze the reception of the public to the content of the accounts about women. The research uses a qualitative approach through reception analysis with Stuart Hall's encoding-decoding theory. Data is collected through interviews, observations, and documentation. The subjects were active followers of the @dailyhaid Instagram account selected based on certain criteria using purposive sampling techniques. The research object on the contents of the @dailyhaid account was uploaded until December 28, 2023. As for the results of the research, the @dailyhaid account improves public understanding of women's fiqh through the delivery of attractively packed messages and the offer of free consultations. While reception analysis based on Stuart Hall's encoding-decoding theory on the expertise of the alleged perpetrator shows five dominant positions and two negotiating positions. The reception of the audience to the content of the message indicates six dominant positions and one negotiating position. The audience's reception to the visualization and narration of the content is in the dominant position. No informant in this study showed digestion in opposition positions.